Government integrity and corporate investment efficiency - Jing Du; Wanfu Li; Bin Lin; Yu Wang (China Journal of Accounting Research, 2018)
We explore the relation between government integrity and firms' investment efficiency in the context of China's deepening reforms and its strengthening the social credit system. We find that government integrity is positively associated with the investment efficiency of listed companies in China. Government integrity is negatively related to corporate underinvestment, but insignificantly related to corporate overinvestment. Higher government integrity reduces underinvestment in non-state-owned firms, but this relation is not significant in state-owned firms. Furthermore, we find that the negative relation between government integrity and underinvestment is only significant for firms in industries that receive supportive government policies. This study enriches research on corporate investment by adopting the perspective of government integrity, and supplements the literature on government integrity and its economic consequences. Our study also provides micro-level empirical evidence that strengthening government integrity will promote the economic transformation of China.
Keywords: 650; Government integrity; Investment efficiency; Types of share ownership; Industrial policies' support